2020
DOI: 10.1101/2020.10.11.20210690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between TM6SF2 rs58542926 T/C gene polymorphism and significant liver fibrosis: A meta-analysis

Abstract: Aim: To further explore the association between Transmembrane 6 superfamily member 2(TM6SF2) rs58542926 T/C gene polymorphism and hepatic fibrosis. Materials and Methods: In this study the MEDLINE, PubMed, EMBASE, and CENTRAL databases were queried from inception to March 21, 2020. According to inclusion and exclusion criteria; case control studies assessing the relationship between TM6SF2 rs58542926 T/C gene polymorphism and significant liver fibrosis were selected. NOS scale was used to evaluate the included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…A meta-analysis study on the E167K variant in preventing CAD and conferring risk for NAFLD revealed that the rs58542926 polymorphism is a key regulator of blood lipid characteristics in global studies [62]. Metaanalysis studies have also shown the E167K (rs58542926) polymorphism in TM6SF2 in NAFLD and other human diseases, such as carcinoma and liver fibrosis [42,[62][63][64]. For the H63D polymorphism, 21% of heterozygotes and 2.1% of homozygous variants were present in NAFLD cases in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…A meta-analysis study on the E167K variant in preventing CAD and conferring risk for NAFLD revealed that the rs58542926 polymorphism is a key regulator of blood lipid characteristics in global studies [62]. Metaanalysis studies have also shown the E167K (rs58542926) polymorphism in TM6SF2 in NAFLD and other human diseases, such as carcinoma and liver fibrosis [42,[62][63][64]. For the H63D polymorphism, 21% of heterozygotes and 2.1% of homozygous variants were present in NAFLD cases in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…Another SNP associated with impaired intracellular lipid regulation in the hepatic cells is rs58542926, E167K in the transmembrane 6 superfamily member 2 gene, which has a vital role in the development of liver cirrhosis and HCC [ 17 ]. TM6SF2 gene is located on chromosome 19, its expression produces the TM6SF2 protein, which is implicated in the risk of NASH and also induces hepatic fibrosis [ 18 ]. The T allele of rs58542926 increases the risk of liver disease and HCC development [ 15 ].…”
Section: Introductionmentioning
confidence: 99%